Analysis of the Effect of Changes in Pitch Ratio and Number of Blades on Cavitation on CPP - Mohammad Danil Arifin; Danny Faturachman; Fanny Octaviani; Karina Adinda Sulaeman (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2020)
Cavitation is a detrimental phenomenon to ship operations because it causes many losses. It caused some effects i.e decreased propeller efficiency, damaged propeller material, lower ship speed, vibration, and extreme noises. In that regard, this research conducts cavitation analysis on controllable pitch propeller (CPP) by varying number of blade i.e. 3, 4 and 5 blades; diameter i.e. 30, 40 cm and 50 cm; also pitch i.e 0.4, 0.6 and 0.8. The research method is carried out by the author in this study by conducting a simulation method based on the CFD approach. The simulation process consists of 3 stage-post processor, solver manager, and post-processor. From the simulation based on the CFD approach result, it was found that propeller rotation has an effect on the pressure ratio value. As the propeller rotation increase, the value of the pressure ratio will increase as well. The value of the pressure ratio in propeller design affects the cavitation area that occurs in the propeller. The percentage of the cavitation area on the propeller has an increasing tendency with the number of blades, rotation, and pitch. On the propeller with diameter 300 mm, 3 blades, pitch 0.8 at rotation 125 rpm no indication of cavitation, then it increases to 1.41% at rotation 175 rpm and keeps getting higher at rotation 225 to be 4.22% from total propeller expanding area. Whereas at rotation 225 rpm and pitch 0.4 is 3.38 %, then it becomes 3.85 % at pitch 0.6, which is getting bigger at pitch 0.8 that is 4.22 %.